The Effect of Kegel Exercises on Urinary Frequency in Urinary Incontinence in the Elderly: Pengaruh Latihan Senam Kegel terhadap Frekuensi Berkemih pada Inkontinensia Urine Lanjut Usia (Lansia) - Maula, Liya Ni’matul; Yunita, Astri; Setyadi, Ahmad Wasis (Napande: Jurnal Bidan, 2024)
Background: Increasing age results in changes in the anatomy and function of the urinary organs, including weakening of the pelvic floor muscles which causes a decrease in the muscles of the urethral opening. Objective: The effect of Kegel exercises on the frequency of urination in the elderly at UPT Tresna Werdha Social Services (UPSTW) Jombang is known. Method: The research design is pre-experimental with a one group pretest - posttest design. The sampling technique was determined by purposive sampling, namely 46 elderly people. The research instrument is a questionnaire. Data analysis used the Wilcoxon test. Results: Before treatment, the majority (58.7%) had abnormal urination frequency and after (93.5%) the urination frequency was normal. The results of data analysis have a sig (2-tailed) value: 0.000, so Ho is rejected. Conclusion: Kegel exercise therapy affects the frequency of urination in elderly people who experience urinary incontinence at UPSTW Jombang. It is best to apply Kegel exercises to the elderly to prevent urinary incontinence